Ambulance Modification for Pap Smear Screening in Nong Suea, Pathum Thani - Larpchareon, Somchai (Journal of Health Science of Thailand, 2018)
In recent years, cervical cancer became the most important cancer in Thai women in terms of mortality and morbidity. High coverage of cervical cancer screening among the risk group could undoubtedly reduce the adverse health impacts. In the past few years, the screening rate fell below 40 percent of the over 35 years old women throughout Pathum Thani province. Active operation was carried out in Nong Suea district by Nong Suea hospital and its allied health centers from the year 2004 to 2007. The interventions consisted of proper health education about cervical cancer and pap smear and a mobile unit for cervical cancer screening among those who lived far away from health centers and were occupied during working hours. The key process of the mobile unit was the modification of an ambulance into a movable temporary pap smear screening room. The objective of this study was to assess the value of the modified ambulance for pap smear screening. During the period, the pap smear rate increased on average 38.53 percent per annum, the intra center service rate increased 26.92 percent per year and mobile service rate increased more rapidly 69.23 percent per year. In the year 2007, The pap smear screening performed within the district, covered 72.18 percent of the registered target population. There were no reported significant problems about the modified ambulance hampering it performance in field application. It, therefore, played both directly and indirectly important roles in pap smear screening in Nong Suea district and became very beneficial for the high risk population in remote areas.